2013
DOI: 10.3389/fpsyg.2013.00268
|View full text |Cite
|
Sign up to set email alerts
|

Early ERPs to faces: aging, luminance, and individual differences

Abstract: Recently, Rousselet et al. reported a 1 ms/year delay in visual processing speed in a sample of healthy aged 62 subjects (Frontiers in Psychology 2010, 1:19). Here, we replicate this finding in an independent sample of 59 subjects and investigate the contribution of optical factors (pupil size and luminance) to the age-related slowdown and to individual differences in visual processing speed. We conducted two experiments. In experiment 1 we recorded EEG from subjects aged 18–79. Subjects viewed images of faces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
37
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(51 citation statements)
references
References 112 publications
8
37
2
Order By: Relevance
“…Most importantly, the correlations between age and both visual and auditory delays remained significant after adjusting for sensory acuity. These results suggest that sensory acuity does not play a significant role in our findings, which is consistent with previous studies arguing that optical and retinal factors cannot fully account for age-related delays in the visual evoked response1415162228.…”
Section: Discussionsupporting
confidence: 93%
“…Most importantly, the correlations between age and both visual and auditory delays remained significant after adjusting for sensory acuity. These results suggest that sensory acuity does not play a significant role in our findings, which is consistent with previous studies arguing that optical and retinal factors cannot fully account for age-related delays in the visual evoked response1415162228.…”
Section: Discussionsupporting
confidence: 93%
“…Consistent with the design of our stimuli, consistent response at an early sensory component (P1) indicated that the stimuli were well matched on low-level visual features. While differences in brain activity in response to low-level visual features persist beyond the P1 (Bieniek, Frei, & Rousselet, 2013) and are evident in the hemodynamic response (Yue et al, 2011), our results suggest that low-level differences indexed by the P1(Rossion & Caharel, 2011) do not account for differences observed at subsequent components in these data. In addition, a robust face-sensitive response (N170) was observed subsequent to this initial component that exhibited limited variability in response to familiarity of expression.…”
Section: Discussioncontrasting
confidence: 58%
“…The age‐related delay that we report here agrees with previous cross‐sectional results, which suggest that face processing slows down from 20 years of age and onwards (Bieniek et al, ; Rousselet et al, , ). However, previous studies could not ascribe these delays to the representation of task‐relevant features, as reported here (see also Rousselet, Ince, van Rijsbergen, & Schyns, ; Schyns, Petro, & Smith, ; Smith, Gosselin, & Schyns, ).…”
Section: Discussionsupporting
confidence: 92%
“…Although feature representation was qualitatively similar across young and older adults, it was delayed by 40 ms and weaker in older adults, in the absence of generic delays in the onset of visual cortical activity in older participants. This suggests that the reported delay occurred at the stages of cortical information processing, and was not due to precortical neural factors; thereby adding to the evidence that processing speed delays are unlikely to be due to bottom‐up optical factors, such as senile miosis, contrast sensitivity (Bieniek, Bennett, Sekuler, & Rousselet, ; Bieniek, Frei, & Rousselet, ), or visual acuity (Price et al, ). Furthermore, we believe that bottom‐up optical factors were unlikely contributors to the observed differences at the neural level, because any bottom‐up factors should affect all neural responses irrespectively of their category, whereas we observed much larger N170 to noise textures in older than in young participants.…”
Section: Discussionmentioning
confidence: 73%